PERANAN LINGKUNGAN SEKOLAH TERHADAP PEMBENTUKAN KARAKTER SISWA PADA SEKOLAH DASAR NEGERI NO. 145 INPRES BAYOWA DI KABUPATEN TAKALAR - Kasmiati Kasmiati; Jumiati Nur; Ainun Jariah (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
The problem formulation of this researcher is what is the role of the school environment in the formation of student character at Public Elementary School No. 145 Bayowa Presidential Instruction in Takalar Regency. This researcher aims to find out how the role of the school environment plays in the formation of student character at Public Elementary School No. 145 Bayowa Presidential Instruction in Takalar Regency. This type of research uses qualitative research, in this research the data collection instruments used are in the form of observation, interviews and documentation. The data analysis techniques in this study used data reduction, data presentation and decision making or verification. The results of this study indicate that the role of the school environment in the formation of student character at Public Elementary School No. 145 Inpres Bayowa in Takalar Regency with indicators of teacher and school principal discipline always advises and teaches students to always come on time and do assignments on time, obey the rules orderly school and maintain cleanliness because when there are students who violate school rules, arrive late and do not maintain cleanliness, they will be punished/rewarded with sanctions. Whereas on honest indicators the teacher and principal always teach students to always have an honest attitude, the teacher always reminds students before doing assignments in class not to copy the work of their friends and the teacher also conveys to students if they get students to copy the work of their friends then students are ready to accept the consequences that given by the teacher while on the indicators of responsibility the teacher and principal always provide support and appreciation to students so that students have good responsibilities.